2022
DOI: 10.1038/s43247-022-00652-x
|View full text |Cite
|
Sign up to set email alerts
|

Global perturbation of stratospheric water and aerosol burden by Hunga eruption

Abstract: The eruption of the submarine Hunga volcano in January 2022 was associated with a powerful blast that injected volcanic material to altitudes up to 58 km. From a combination of various types of satellite and ground-based observations supported by transport modeling, we show evidence for an unprecedented increase in the global stratospheric water mass by 13% relative to climatological levels, and a 5-fold increase of stratospheric aerosol load, the highest in the last three decades. Owing to the extreme injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
114
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(131 citation statements)
references
References 77 publications
17
114
0
Order By: Relevance
“…In addition to direct use of the extinction profiles, for this study we retrieve an estimate of the aerosol particle size by fitting the observed spectral dependence to that predicted by Mie scattering theory for a unimodal lognormal particle size distribution of hydrated sulfuric acid. This is a similar approach to that used in Khaykin et al (2022) where the dependence on particle composition is explored, and the retrieved particle size is shown to be consistent with fall speed estimates.…”
Section: Sage Iii/issmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition to direct use of the extinction profiles, for this study we retrieve an estimate of the aerosol particle size by fitting the observed spectral dependence to that predicted by Mie scattering theory for a unimodal lognormal particle size distribution of hydrated sulfuric acid. This is a similar approach to that used in Khaykin et al (2022) where the dependence on particle composition is explored, and the retrieved particle size is shown to be consistent with fall speed estimates.…”
Section: Sage Iii/issmentioning
confidence: 88%
“…Geostationary satellite imagery shows the early plume in the uppermost levels of the stratosphere at a record‐breaking altitude of 58 km (Carr et al., 2022). The highest reaches of the plume, mostly composed of ice, sublimated rapidly in the warm temperatures of the upper stratosphere (Khaykin et al., 2022), with the main plume descending rapidly to be below 30 km since early February (Legras et al., 2022). A truly remarkable feature of this eruption is the large amount of water vapor in the plume, which satellite measurements show accounts for an increase of 10%–13% in the global stratospheric water vapor mass (Khaykin et al., 2022; Millán et al., 2022), although work using balloon sondes estimates a value closer to 5% (Vömel et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong volcanic eruptions such as the major eruption of mount Pinatubo in 1991 can inject vast amounts of volcanic material—mostly ash and SO 2 —high into the stratosphere which temporarily cools the climate 1 . Since the major eruption of Pinatubo, the most sizable moderate eruptions 2 4 in terms of their impact on stratospheric aerosol load are Sarychev 2009, Nabro 2011, Calbuco 2015, Raikoke 2019 and Hunga 2022.…”
Section: Introductionmentioning
confidence: 99%